50=(L)(L-3)

Simple and best practice solution for 50=(L)(L-3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 50=(L)(L-3) equation:


Simplifying
50 = (L)(L + -3)

Reorder the terms:
50 = L(-3 + L)
50 = (-3 * L + L * L)
50 = (-3L + L2)

Solving
50 = -3L + L2

Solving for variable 'L'.

Reorder the terms:
50 + 3L + -1L2 = -3L + 3L + L2 + -1L2

Combine like terms: -3L + 3L = 0
50 + 3L + -1L2 = 0 + L2 + -1L2
50 + 3L + -1L2 = L2 + -1L2

Combine like terms: L2 + -1L2 = 0
50 + 3L + -1L2 = 0

Begin completing the square.  Divide all terms by
-1 the coefficient of the squared term: 

Divide each side by '-1'.
-50 + -3L + L2 = 0

Move the constant term to the right:

Add '50' to each side of the equation.
-50 + -3L + 50 + L2 = 0 + 50

Reorder the terms:
-50 + 50 + -3L + L2 = 0 + 50

Combine like terms: -50 + 50 = 0
0 + -3L + L2 = 0 + 50
-3L + L2 = 0 + 50

Combine like terms: 0 + 50 = 50
-3L + L2 = 50

The L term is -3L.  Take half its coefficient (-1.5).
Square it (2.25) and add it to both sides.

Add '2.25' to each side of the equation.
-3L + 2.25 + L2 = 50 + 2.25

Reorder the terms:
2.25 + -3L + L2 = 50 + 2.25

Combine like terms: 50 + 2.25 = 52.25
2.25 + -3L + L2 = 52.25

Factor a perfect square on the left side:
(L + -1.5)(L + -1.5) = 52.25

Calculate the square root of the right side: 7.228416147

Break this problem into two subproblems by setting 
(L + -1.5) equal to 7.228416147 and -7.228416147.

Subproblem 1

L + -1.5 = 7.228416147 Simplifying L + -1.5 = 7.228416147 Reorder the terms: -1.5 + L = 7.228416147 Solving -1.5 + L = 7.228416147 Solving for variable 'L'. Move all terms containing L to the left, all other terms to the right. Add '1.5' to each side of the equation. -1.5 + 1.5 + L = 7.228416147 + 1.5 Combine like terms: -1.5 + 1.5 = 0.0 0.0 + L = 7.228416147 + 1.5 L = 7.228416147 + 1.5 Combine like terms: 7.228416147 + 1.5 = 8.728416147 L = 8.728416147 Simplifying L = 8.728416147

Subproblem 2

L + -1.5 = -7.228416147 Simplifying L + -1.5 = -7.228416147 Reorder the terms: -1.5 + L = -7.228416147 Solving -1.5 + L = -7.228416147 Solving for variable 'L'. Move all terms containing L to the left, all other terms to the right. Add '1.5' to each side of the equation. -1.5 + 1.5 + L = -7.228416147 + 1.5 Combine like terms: -1.5 + 1.5 = 0.0 0.0 + L = -7.228416147 + 1.5 L = -7.228416147 + 1.5 Combine like terms: -7.228416147 + 1.5 = -5.728416147 L = -5.728416147 Simplifying L = -5.728416147

Solution

The solution to the problem is based on the solutions from the subproblems. L = {8.728416147, -5.728416147}

See similar equations:

| -4n(2n+3)=8 | | 5x^2-4x+1=673 | | -5t^2+24t+36=0 | | -7v-40=9(v-8) | | (39200+-8x)=-770 | | 2(w+9)=7w-2 | | 8(4900-x)=770 | | 8v-7=-3(v+6) | | -6x+5.4=6.3+1.2x | | x/3=15/2 | | (1/(ab))/(1/(ab^2))/(1/(a^2b)) | | 2x(x+3)=-15 | | 216=45t | | x^4(a-b)+16(b-a)=0 | | 0.30x+0.05(20-x)=0.10(-10) | | Log(x^2-9)-3=log(x+3) | | 1/2w-2/3=2/3 | | H*t=128t-16t^2 | | 3x/9x= | | 9-5/2= | | (5x-6)(2x+9)= | | 0=-0.125x^2+0.35x+0.75 | | 4(x-2)4x+10= | | Log(x^2-9)-log(x+3)=3 | | y=-0.125x^2+0.35x+0.75 | | -2v+34=8(v+3) | | (4x^2-3x^3)-(8x^2-5x^3)= | | 17z-6z+3= | | 5w^2-3w=17 | | 9x^2/lnx | | 8(u+4)=-2u+12 | | 100=-0.1x+1 |

Equations solver categories